Association Between Prenatal Sonographic Findings of Duodenal Obstruction and Adverse Outcomes. (27th July 2016) - Kim, Ji Ye; You, Ji Yeon; Chang, Kylie Hae-jin; Choi, Suk-Joo; Oh, Soo-young; Seo, Jeong-Meen; Roh, Cheong-Rae; Kim, Jong-Hwa
Abstract : Objectives: The purpose of this study was to evaluate the association of prenatal sonographic findings with adverse outcomes and the causes of duodenal obstruction. Methods: A total of 59 cases of congenital duodenal obstruction were included in this study. The sonographic findings, including the degree of duodenal dilatation, polyhydramnios, and their change over gestation, were investigated. Adverse outcomes were defined as fetal death in utero, postnatal death, and gastrointestinal complications requiring readmission or reoperation during the follow‐up period. The cause of duodenal obstruction was also assessed. Results: Among the patients studied, 2 (3.4%) had fetal death in utero and 2 (3.5%) had postnatal death. Gastrointestinal complications requiring readmission or reoperation occurred in 10.9%. In the cases with or without adverse outcomes, no significant differences were observed in the prenatal sonographic findings: maximum duodenal dilatation, mean amniotic fluid index, and the changes in these parameters with advancing gestation. The cases with adverse outcomes were associated with a younger gestational age at delivery compared to the cases without adverse outcomes. Notably, the degree of duodenal dilatation and amniotic fluid volume were greater in duodenal atresia than in other causes of obstruction, including duodenal stenosis, a duodenal web, and an annular pancreas. In the study population, the overall postoperative survival rate was 98.2%. Conclusions: Prenatal sonographic findings of duodenal obstruction were not associated with adverse outcomes; however, they may be helpful for differentiating the cause of duodenal obstruction.